Plaque echolucency and the risk of ischaemic stroke in patients with asymptomatic carotid stenosis within the first asymptomatic carotid surgery trial (ACST-1) - Huibers, A; de Borst, G; Bulbulia, R; Pan, H; Halliday, A (Elsevier, 2015)
Objective/Background On ultrasound, potentially “high risk” carotid plaques may appear echolucent. In this study, whether a confident classification of echolucent plaque was a predictor of future ipsilateral ischaemic stroke in asymptomatic patients randomized to medical therapy in the Asymptomatic Carotid Surgery Trial-1 (ACST-1) was assessed. Methods We performed a post-hoc analysis of 814 ACST-1 patients randomized to medical therapy alone with baseline plaque assessment classified as definitely echolucent (>25% soft plaque) or nonecholucent (<25% soft plaque). KaplaneMeier survival curves were used to compare cumulative rates of ipsilateral ischaemic stroke in both groups. Results In the first 5 years after randomization, a significantly higher risk of ipsilateral stroke was observed in patients with definitely echolucent plaques (8.0%; 95% confidence interval [CI] 6.4-9.6) when compared with patients with definitely nonecholucent plaques (3.1%; 95% CI 2.1e4.1;p=.009). After adjustments for other risk factors, plaque echolucency was associated with a 2.5-times increased risk of ipsilateral ischaemic stroke (hazard ratio 2.52; 95% CI 1.20e5.25;p=.014). Use of lipid-lowering therapy was low in both groups during the first 5 years after randomization but rose sharply during years 5e10 of follow-up, and was significantly more likely to be prescribed for patients with echolucent plaques (p=.001). The risk of ipsilateral ischaemic stroke at 10 years was similar for both groups of patients (p=.233). Conclusion Although the numbers of events in this study was low, definite plaque echolucency (>25% soft plaque) was associated with a higher 5-year ipsilateral stroke risk in ACST-1 and may therefore help to identify patients at increased risk of stroke for whom carotid intervention may be particularly beneficial.